Aggressive Periodontitis and Palmoplantar Keratoderma: Papillon–Lefèvre Syndrome in an 11‐Year‐Old Nepalese Girl - Jenisha Bhattarai; Sanish Pokhrel; Yogendra Poudel; Ujjwal Rimal (Clinical Case Reports, 2026)
ABSTRACT Papillon–Lefèvre syndrome is a rare autosomal recessive disorder characterized by palmoplantar keratoderma and aggressive periodontitis. We report an 11‐year‐old Nepalese girl presenting with severe periodontal destruction and characteristic cutaneous manifestations. Clinical and radiographic findings established the diagnosis. Early multidisciplinary management is essential to preserve function and improve quality of life.